Implementing Outcome-based Care in Pediatric Psychiatry: Early Results and Overcoming Barriers. Issue 1 (January 2019) - Krishna, Rajeev; Valleru, Jahnavi; Smith, Whitney
Abstract : Background: Poor utilization of standardized outcome measures for monitoring patient care and progress in mental health services is evident. The objective of this work was to implement computerized diagnostic and history assessments for outpatient mental health visits in the ambulatory psychiatric clinic of a large pediatric health system. Methods: A computerized assessment system was created for the iPad to administer and score a series of validated diagnostics before new patient and follow-up appointments with a psychiatry provider. Outcome measures were a percentage of completed assessments, provider satisfaction, and patient satisfaction. Results: Across all outpatient psychiatry clinics, screener completion rate for new patients increased from 0% to 90% within 1 year of implementation and sustained within 3σ process control limits for 2 years. Return visit assessment completion increased from 0% to 80%. The most substantial completion rate increase was related to scheduling assessment time as part of the visit. Assessment of provider and patient satisfaction through surveys before and after the implementation showed 94% of providers felt that visit efficiency had improved, and overall opinion of the system was highly positive. Patients also reported high satisfaction with the assessment process (4.1 on Likert scale 0–5, 5 = very positive). Conclusions: This quality improvement program demonstrates strategies for overcoming barriers to the use of standardized assessments in outpatient psychiatry. We show that a large pediatric mental health system can achieve systematic outcome data collection with minimal disruption to routine clinical care.